Conceptions and Evaluative Practices in University Teachers of Scientific Careers That Implement a Competency-Based Curriculum; [Concepções E Práticas Avaliativas Em Professores Universitários de Carreiras Científicas Que Implementam Um Currículo Baseado Em Competências]; [Concepciones y Prácticas Evaluativas en Docentes Universitarios de Carreras Científicas Que Implementan Un Currículum por Competencias] - Rios-Munoz, D (Fundacao Cesgranrio, 2024)
In this paper, the results of a research on conceptions and evaluative practices of professors of chemical, pharmaceutical and biochemical sciences at a public university in Chile are analyzed. A survey, four focus groups and two in-depth interviews were applied. 87% of the teachers and main directors participated. The results are related to the meanings, purposes, functions, and intentions of learning evaluation, which teachers express and apply in a curricular innovation by competencies. The existence of conceptions and practices mainly of an instrumental and objectifying type of evaluation is concluded, more in line with an academic curriculum, oriented by objectives and contents, than a competency-based curriculum that seeks professional performance in the context of changes. © 2024 Fundacao Cesgranrio. All rights reserved.